EphA4 loss improves social memory performance and alters dendritic spine morphology without changes in amyloid pathology in a mouse model of Alzheimer’s disease - Poppe, Lindsay (Alzheimers Res Ther, 2019)
BACKGROUND: EphA4 is a receptor of the ephrin system regulating spine morphology and plasticity in the brain. These processes are pivotal in the pathophysiology of Alzheimer’s disease (AD), characterized by synapse dysfunction and loss, and the progressive loss of memory and other cognitive functions. Reduced EphA4 signaling has been shown to rescue beta-amyloid-induced dendritic spine loss and long-term potentiation (LTP) deficits in cultured hippocampal slices and primary hippocampal cultures. In this study, we investigated whether EphA4 ablation might preserve synapse function and ameliorate cognitive performance in the APPPS1 transgenic mouse model of AD. METHODS: A postnatal genetic ablation of EphA4 in the forebrain was established in the APPPS1 mouse model of AD, followed by a battery of cognitive tests at 9 months of age to investigate cognitive function upon EphA4 loss. A Golgi-Cox staining was used to explore alterations in dendritic spine density and morphology in the CA1 region of the hippocampus. RESULTS: Upon EphA4 loss in APPPS1 mice, we observed improved social memory in the preference for social novelty test without affecting other cognitive functions. Dendritic spine analysis revealed altered synapse morphology as characterized by increased dendritic spine length and head width. These modifications were independent of hippocampal plaque load and beta-amyloid peptide levels since these were similar in mice with normal versus reduced levels of EphA4. CONCLUSION: Loss of EphA4 improved social memory in a mouse model of Alzheimer’s disease in association with alterations in spine morphology.